Clinical Evaluation of Avasthānusāra Pakshāghāta Treatment Protocol (APTP) in Post-Stroke Hemiplegia: A Case Series - Dr. Asharani Medidar; Dr. Manu R. (The Bioscan, 2025)
This case series evaluates the effectiveness of Avasthanusara Pakshaghata Treatment Protocol (APTP), a personalized Ayurvedic approach, in managing post-stroke hemiplegia across multiple patients. The interventions are tailored to the disease stage (Ama-Avastha and Nirama-Avastha), incorporating external therapies. This series presents clinical observations, treatment protocols, and outcomes to highlight the potential benefits of APTP in neurological rehabilitation. Keywords Avasthanusara, Pakshaghata, Ama-Avastha, Nirama-Avastha.